Association of SGK1 Polymorphisms With Susceptibility to Coronary Heart Disease in Chinese Han Patients With Comorbid Depression - Han, Wenxiu; Zhang, Haixia; Gong, Xiaoxue; Guo, Yujin; Yang, Mengqi; Zhang, Hailiang; Zhou, Xueyuan; Li, Gongying; Liu, Yuanyuan; Jiang, Pei; Yan, Genquan (Frontiers in Genetics, 2019)
There is a strong link between heart disease and depression, both of which are closely related to life time stress exposure. Serum and glucocorticoid regulated kinase 1 (SGK1) is a stress-responsive gene with a pivotal role in both heart and brain. To determine the role of SGK1 polymorphisms (rs2758151, rs1743963, rs9493857, rs1763509, rs9376026, rs9389154) in susceptibility to comorbid coronary heart disease (CHD) and depression, we conducted a hospital-based case-control study involving 257 CHD cases (including 69 cases with depression and 188 cases without depression) and 107 controls in a Chinese Han population. Six single nucleotide polymorphisms (SNPs) in the SGK1 gene were successfully genotyped by polymerase chain reaction-ligase detection reaction (PCR-LDR) assay. Our results showed no significant differences in SGK1 genetic polymorphisms between CHD patients and controls, whereas significant associations were observed between SGK1 SNPs (rs1743963, rs1763509) and the development of depression in CHD patients (P=0.018 by genotype, P=0.032 by allele; P=0.017 by genotype, P=0.003 by allele respectively). However, none of these associations remained significant after Bonferroni correction (P=0.054 for rs1743963; P=0.051 for rs1763509). Interestingly, both the GG genotype of SGK1 rs1743963 and AA genotype of SGK1 rs1763509 were associated with a higher risk of depression in CHD patients; for rs1763509, the PHQ-9 scores in the carriers of the risk genotype for comorbid depression, AA, were significantly higher than GG and AG carriers (P=0.008). Notably, haplotype analysis indicated that haplotype GGA significantly increased the risk of depression in CHD patients (P=0.011, odds ratio (OR) =1.717, 95% CI=1.132-2.605), whereas haplotype AAG may be a protective factor for CHD patients with comorbid depression (P=0.038, OR=0.546, 95% CI=0.307-0.972). It should be noted that only the significance of haplotype GGA survived after Bonferroni adjustment (P=0.044) and no significant differences were found for other SGK1 SNPs (rs2758151, rs9493857, rs9376026, rs9389154) between CHD patients with and without depression. These findings, for the first time, elucidate the important role of SGK1 variants in the comorbidity of CHD and depression.